Literature Review: How to Implement Work Based Learning in Vocational Education - Nafisa Firmania (International Conference on Industrial Revolution for Polytechnic Education, 2019)
Vocational Education is education using a dualsystem. The dual system in question is learning carried out intwo places, namely in schools for Vocational High Schools orlearning carried out on campus for vocational students andlearning that is carried out in the world of work or industry.Learning carried out in two places must be able to balancetheory and practice. In order for a balance to occur there is aneed for an adequate learning model. One learning model thatis suitable for use in vocational education is Work BasedLearning (WBL). WBL is a learning model that teachesindividuals to be ready to work. In the world of vocationalpractice, it has become an important part, but if the practice isgood, but the theory is not strong, then someone can be saidnot to succeed in a career. WBL has several characteristics thatare closely related to vocational education.